Barriers to safety program implementation in the construction industry - Buniya, M.K. (Ain Shams University, 2021)
Poor safety performance is a serious problem in the construction industry. Safety program implementation has always been one of the most successful actions to reduce construction accidents. This research aims to identify barriers to the implementation of safety programs in the construction industry. It begins with identifying barriers to the implementation of safety programs from the literature review. Further barriers were identified from semi-structured interviews conducted with experts in the construction industry in Iraq. The exploratory factor analysis (EFA) technique was used to evaluate data collected from the survey, reduce the number of factors and establish relationships between variables. Based on the analysis, the 12 barriers were grouped into four dimensions: non-conductive work climate, poor governance, poor safety awareness, and unsupportive industry norms. Partial Least Square Structural Equation Model (PLS-SEM) was conducted to validate the EFA results through assessing the relationships between constructed and items. It is recommended that a system of governance at the national level is developed to take these barriers down and improve safety performance in the construction industry. Â© 2020 THE AUTHORS